Work Behavior Analysis of Indonesian Civil Servants Using Social Media Interactions - Ari Agustina; Ratminto Ratminto (Magister Ilmu Administrasi Publik, 2023)
This research examined Indonesian civil servants' work behavior using social media interactions. A hermeneutic approach was used to ascertain the meaning of an individual’s actions using text in social media interactions. The results showed that the work behavior of Indonesian civil servants tends to be negative and is primarily due to the unequal distribution of workload. First, this study uses a collection of data obtained from Twitter. Second, the data taken is selected based on the topic of work behavior. This research implies that work behavior needs to be monitored and managed appropriately to enhance public sector organizations' achievement and keep employees in proper conditions. Furthermore, work behavior management can be improved by evenly distributing the workload among employees. Negative work behavior leads to decreased employee performance, which causes dissatisfaction in public services. Work behavior analysis using social media interactions in the public sector is a new theme that needs to be explored in public administration practice. This is a critical topic of research as it can affect the achievements of an organization due to the support of rapid technological developments.